Evaluating System Efficiencies and Service Delivery of Immigrant Population in South Africa and United States - Dinbabo, Mulugeta F; Ile, Isioma; Majee, Wilson; Belebema, Michael; Boadu, Evans (African Human Mobility Review, 2021)
Recently, global issues on the migration and development discourse have reemerged and the literature has been expanding rapidly. However, most of the research has not taken into account the connection between the migrationdevelopment nexus in the context of social service delivery. In general, discussions and systematic reflections on the international comparison between South Africa and United States is completely absent or rarely found in the academic debates. Both countries were selected as sites for this study given the high migrant populations. Using a quantitative research methodology this study assessed and evaluated the system efficiencies and service delivery of immigrant population in South Africa and United States of America. Structured questionnaires were administered to selected African immigrants in the two case study areas (Cape Town, South Africa and Columbia, Missouri). The surveys provided data for a range of indicators that helped in evaluating the system efficiencies and service delivery of immigrant population.